2023
DOI: 10.3390/w15020285
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rainfall Partitioning and Estimation of the Utilisation of Available Water in a Monoculture Beech Forest and a Mixed Beech-Oak-Linden Forest

Abstract: Monoculture forests formed by Fagus sylvatica L. belong to one of the most sensitive forest ecosystems, mainly at low altitudes. Cultivation of this species in mixed stands should reduce its sensitivity to drought in the vegetation period, which is why we researched the water balance in one pure-beech (i.e., monoculture) and one beech–oak–linden (i.e., mixed) forest. This research was carried out in Drahanská vrchovina in the Czech Republic in the period 2019–2021. The total precipitation was measured, togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…SWC was measured only in stands with deciduous tree species (beech, hornbeam and oak) that were considered similar for this purpose. While beech and hornbeam exhibit similar water partitioning, oak has usually significantly more throughfall and less stemflow and can reach higher transpiration rates especially under drier conditions (Novosadová et al, 2023). Our LAI indexes as well as root density measurements indicated that the admixture of oak in these conditions did not have a clear effect on these two parameters (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…SWC was measured only in stands with deciduous tree species (beech, hornbeam and oak) that were considered similar for this purpose. While beech and hornbeam exhibit similar water partitioning, oak has usually significantly more throughfall and less stemflow and can reach higher transpiration rates especially under drier conditions (Novosadová et al, 2023). Our LAI indexes as well as root density measurements indicated that the admixture of oak in these conditions did not have a clear effect on these two parameters (Table 1).…”
Section: Discussionmentioning
confidence: 99%